Past and Future Developments in the Economics of Relational Contracts - Matthias Fahn; W. Bentley MacLeod; Gerd Muehlheusser (Institute of Labor Economics (IZA), 2023)
This paper was written as an editorial preface to a "Symposium on Relational Contracts", that was jointly edited by the three authors, and that will appear in the Journal of Institutional and Theoretical Economics (JITE). The Symposium contains eleven contributions to the economics of relational contracts, written by many of the leading scholars in the field. This editorial preface provides a narrative that positions the eleven contributions within the broader context of relational contracts, as addressed by economists, and it explains how these contributions are linked to each other.
Keywords: D82; D85; C73; 330; relational contracts; organizational economics